Roles of mitochondria in neutrophils - Cao, Ziming; Zhao, Meng; Sun, Hao; Hu, Liang; Chen, Yunfeng; Fan, Zhichao (Frontiers in Immunology, 2022)
Neutrophils are the most abundant leukocyte in human blood. They are critical for fighting infections and are involved in inflammatory diseases. Mitochondria are indispensable for eukaryotic cells, as they control the biochemical processes of respiration and energy production. Mitochondria in neutrophils have been underestimated since glycolysis is a major metabolic pathway for fuel production in neutrophils. However, several studies have shown that mitochondria are greatly involved in multiple neutrophil functions as well as neutrophil-related diseases. In this review, we focus on how mitochondrial components, metabolism, and related genes regulate neutrophil functions and relevant diseases.